Holistic approach to education and upbringing: Contradictory to the general assumption of life - Mihajlović Ljubiša M.; Mihajlović Milica Lj; Mihajlović Nevenka K. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2014)
Holistic education is a compprehensive view of education based on the assumption that each individual finds his own identity, meaning and objective in life through the connection with the community, nature and human values such as compassion and peace. Within holistic education the teacher is viewed not as an authority figure who guides and controls, but rather as a 'friend', a facilitator of learning: a guide and a companion in gaining experience. The norm is cooperation rather than competition. However, is this possible in real life? The answer is simple - it is not. Why? The reason why lies in the foundation of life itself: a molecule built in such a way that it does not permit such an idealistic approach to life, and therefore, to education. It is a DNK molecule: the molecule of life exhibiting, among other, the following characteristics: it seeks procreation, and exhibits the tendency of eternal struggle, competition. This is in stark opposition to holistic approach to education which does not recognize competition, struggle, gradation and rivalry. The development of an advanced and socially responsible society demands partial, measured application of holism. This needs to be reflected in education as well: approved competition, clear and fair gradation, the best in certain areas become the elite, with the rest following or to be found solutions in accordance with their abilities.